Recessive MYPN mutations cause cap myopathy with occasional nemaline rods. Issue 3 (20th March 2017) - Lornage, Xavière; Malfatti, Edoardo; Chéraud, Chrystel; Schneider, Raphaël; Biancalana, Valérie; Cuisset, Jean‐Marie; Garibaldi, Matteo; Eymard, Bruno; Fardeau, Michel; Boland, Anne; Deleuze, Jean‐François; Thompson, Julie; et al.
Abstract : Congenital myopathies are phenotypically and genetically heterogeneous. We describe homozygous truncating mutations in MYPN in 2 unrelated families with a slowly progressive congenital cap myopathy. MYPN encodes the Z‐line protein myopalladin implicated in sarcomere integrity. Functional experiments demonstrate that the mutations lead to mRNA defects and to a strong reduction in full‐length protein expression. Myopalladin signals accumulate in the caps together with alpha‐actinin. Dominant MYPN mutations were previously reported in cardiomyopathies. Our data uncover that mutations in MYPN cause either a cardiac or a congenital skeletal muscle disorder through different modes of inheritance. Ann Neurol 2017;81:467–473